1976
DOI: 10.1111/j.1365-2133.1976.tb05168.x
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus controlled by dapsone

Abstract: Three uncomplicated cases of pemphigus were clinically controlled by dapsone. Improvement was associated with decreasing titres of circulating intercellular antibodies. Interestingly, the sera from one case of pemphigus foliaceus contained intercellular antibodies found in the Malpighian and basal cell layers using the fluorescent technique and in the granular layer using the peroxidase technique. These findings suggest that the intercellular antibodies in pemphigus vulgaris and pemphigus foliaceus are similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] Dapsone was used as monotherapy in six (16%) patients. There were 37 patients in 13 reports who were treated with dapsone.…”
Section: Pemphigus Vulgarismentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] Dapsone was used as monotherapy in six (16%) patients. There were 37 patients in 13 reports who were treated with dapsone.…”
Section: Pemphigus Vulgarismentioning
confidence: 99%
“…The use of dapsone in the treatment of pemphigus vulgaris is mostly reported in those cases described as dermatitis herpetiformis associated with pemphigus [6,[17][18][19], The use of this agent as a substitute for corticosteroids in unquestionable cases with this malady has, to the best of our knowledge, been reported on one occasion only [4].…”
Section: Discussionmentioning
confidence: 99%
“…In one, dapsone was added to the treatment after a failure of combined pred nisone and methotrexate therapy to control the disease completely. It is suggested that dapsone may offer a means in an attempt to minimize adverse reactions met with during the long corticosteroid regimen required in pemphigus.Reports on well-established cases with pemphigus vulgaris effectively controlled by dapsone are, so far, sporadic and as yet revealed no reliable means for the selection of cases for this therapy [1][2][3][4]. However, the fre quencies of various side effects associated with the present accepted modali ties of treatment lend these reports a special practical interest [5].…”
mentioning
confidence: 99%
“…Other anti-inflammatory drugs have been used to treat pemphigus and these include: dapsone, minocycline, or tetracycline with nicotinamide. Immunosuppressive agents have also been used and these include: azathioprine, methotrexate, cyclophosphamide, gold, chlorambucil, and mycophenolate mofetil [105][106][107][108][109][110][111]. Patients with severe disease in whom corticosteroids and immunosuppressive agents are not able to control the disease, intravenous corticosteroids, plasmapheresis, extracorporeal photopheresis, and intravenous cyclophosphamide have been used [112][113][114][115][116]; however, the mortality and morbidity associated with these approaches is not trivial.…”
Section: Pemphigusmentioning
confidence: 99%